The impact of septoplasty on health‐related quality of life in paediatric patients. (4th February 2016) - Anderson, K.; Ritchie, K.; Chorney, J.M.; Bezuhly, M.; Hong, P.
Abstract : Objectives: To assess the impact that septoplasty had on health‐related quality of life (HRQoL) in paediatric patients and to determine whether there were patient characteristics that predicted better outcomes. Design: Retrospective cohort study. Setting: Academic paediatric otolaryngology practice. Participants: All paediatric patients who underwent septoplasty during the study period. Main outcome measures: The current HRQoL was assessed using the Paediatric Quality of Life Inventory (PedsQL). The Glasgow Children's Benefit Inventory (GCBI) was used to evaluate the perceived change in HRQoL following septoplasty. Results: A total of 29 patients (16 boys, mean age 13 years) and their caregivers responded (response rate of 72.5%). There was a statistically significant improvement in HRQoL following septoplasty, as demonstrated by the positive mean GCBI subscores and the total GCBI score (35.1, sd  = 28.4). The total mean PedsQL score for child self‐report was 95.2 (sd  = 6.9) and for parent‐proxy report was 91.8 (sd  = 8.6), which indicated good current HRQoL. The enhancement in HRQoL post‐septoplasty was moderately correlated with self‐reported degree of nasal obstruction pre‐septoplasty ( r  = 0.621 for total GCBI). Also, there were differences in GCBI scores between the groups of children who wanted to have the surgery versus those who did not want to have the surgery. Conclusions: There was a significant positive change in HRQoL following paediatric septoplasty in our study population. Children who reported more severe nasal obstruction and those who wanted to have the surgery were more likely to experience enhancement of HRQoL following their surgery.